A Systematic Implementation of Six Sigma for Productivity Enhancement in Small-Scale Engineering Industries - Amarishkumar J Patel; Sunilkumar N Chaudhari (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
In today’s highly competitive manufacturing environment, small-scale industries encounter significant challenges in maintaining consistent productivity and quality due to resource constraints and process variability. This study presents a systematic application of the Six Sigma DMAIC (Define–Measure–Analyze–Improve–Control) methodology for productivity enhancement in a small-scale engineering enterprise, Prismetic Industries. The research adopts a case-based approach, integrating process mapping, measurement system analysis, and statistical tools to identify and mitigate sources of inefficiency in machining operations. During the Define and Measure phases, key process parameters and critical-to-quality characteristics were identified to establish a baseline understanding of process performance. Detailed analysis revealed that inconsistencies in tool wear, fixture setup, and inspection practices were the primary causes of variation affecting both quality and throughput. Focused improvement actions were implemented through preventive maintenance, standardization of setup procedures, and operator training programs, resulting in marked improvement in process stability, quality consistency, and overall productivity. The Control phase emphasized long-term sustainability of these improvements through regular process monitoring, control charts, and visual management techniques. The results confirmed that the Six Sigma approach not only improved operational performance but also enhanced process discipline and employee engagement across the organization. This study demonstrates that with structured methodology, management commitment, and team collaboration, small-scale industries can effectively achieve productivity enhancement and quality improvement using Six Sigma principles.